Promoting Equity in Public Health: Addressing Inequality and Social Disparities - Abdullaha Al Mamun; Morshed Alam (Health Science Reports)
ABSTRACT Background Health inequalities remain a global issue, deeply rooted in social, economic, and environmental determinants that shape health outcomes. This editorial examines these disparities and critiques the World Health Organization's (WHO) health definition to address the historical and systemic injustices that perpetuate health inequities. Methods This paper synthesizes research and expert perspectives on the fundamental causes of health inequities, focusing on social determinants such as income inequality, environmental hazards, and systemic discrimination. Results Findings highlight significant disparities in healthcare access and outcomes, particularly among marginalized populations affected by factors like income, race, and geographic location. This underscores the need for tailored, equity‐centered approaches to healthcare. Conclusions A coordinated global approach that addresses both environmental and social determinants of health is essential to create equitable and resilient health systems.